Real-world effectiveness of RSVpreF vaccination during pregnancy against RSV-associated lower respiratory tract disease leading to hospitalisation in infants during the 2024 RSV season in Argentina (BERNI study): a multicentre, retrospective, test-negative, case–control study - Pérez Marc, Gonzalo; Vizzotti, Carla; Fell, Deshayne B; Di Nunzio, Lucila; Olszevicki, Santiago; Mankiewicz, Shauna Wolf; Braem, Virginia; Rearte, Ramiro; Atwell, Jessica E; Bianchi, Alejandra; Fuentes, Nora; Zadoff, Romina; et al. (The Lancet infectious diseases, 2025)
In March, 2024, Argentina became the first country to implement a national maternal immunisation programme with bivalent respiratory syncytial virus (RSV) prefusion F vaccine (RSVpreF) as the primary strategy to prevent RSV disease among infants. We aimed to evaluate vaccine effectiveness against RSV-associated lower respiratory tract disease (LRTD) and severe LRTD leading to hospitalisation among infants during the first season after implementation. A multicentre, retrospective, test-negative, case-control study was done during the 2024 RSV season in 12 hospitals across Argentina (BERNI study). We included infants aged 6 months or younger who were hospitalised with LRTD between April 1 and Sept 30, 2024, and tested for RSV using PCR or indirect immunofluorescence; cases were infants with any positive RSV test and controls were PCR-confirmed negative for RSV. Infants were considered born to an RSVpreF-vaccinated pregnant woman if RSVpreF was received between 32+0/7 weeks and 36+6/7 weeks of gestation and 14 days or more before delivery. We estimated vaccine effectiveness against RSV-associated LRTD requiring hospitalisation (primary outcome) and RSV-associated severe LRTD requiring hospitalisation (key secondary outcome) by comparing the odds of RSVpreF vaccination during pregnancy among infant cases versus controls using multilevel logistic regression adjusted for potential confounders. Of 633 infants hospitalised for LRTD between April 1 and Sept 30, 2024, 505 (286 cases and 219 controls) met full eligibility criteria for inclusion in the primary vaccine effectiveness analysis; 51 (18%) cases and 109 (50%) controls were born to individuals who received RSVpreF during pregnancy. Vaccine effectiveness against RSV-associated LRTD leading to infant hospitalisation was 78·6% (95% CI 62·1–87·9) from birth to age 3 months and 71·3% (53·3–82·3) from birth to age 6 months. Effectiveness against RSV-associated severe LRTD leading to hospitalisation was 76·9% (45·0–90·3) from birth to age 6 months. Three RSV-associated in-hospital deaths occurred, all among infants whose mothers did not receive RSVpreF during pregnancy. These real-world estimates for the 2024 RSV season in Argentina show high RSVpreF effectiveness against RSV-associated LRTD and severe LRTD leading to hospitalisation from birth to age 3 months and sustained to age 6 months. Pfizer. For the Spanish translation of the abstract see Supplementary Materials section.